2014
DOI: 10.1369/0022155414532654
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of SOX2 and OCT4 Indicates Radiation Resistance and an Independent Negative Prognosis in Cervical Squamous Cell Carcinoma

Abstract: SummaryRadiotherapy (RT) as a preoperative or postoperative adjuvant or primary treatment is the most common management modality for locally advanced cervical cancer. Radioresistance of tumor cells remains a major therapeutic problem. Consequently, we aimed to explore if the stem cell biomarkers SOX2 and OCT4 protein could be used to predict radioresistance in patients with locally advanced cervical squamous cell carcinoma (LACSCC). These 132 patients were divided into two groups (radiation-resistant and radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 44 publications
5
74
0
Order By: Relevance
“…These findings correlates with earlier study reporting higher expression of OCT4 in premalignant and malignant cervical tumors; and its association with poor disease‐free survival and overall survival in patients with cervical cancer . The results holds significance as literature suggests the importance of OCT4 expression in resistance to radiotherapy in tumor cells and as predictors of poor survival . These support the hypothesis that OCT4 works as an oncogene in cervical carcinogenesis; more so when the knockdown of OCT4 have been shown to result in tumor cell apoptosis, decreased tumor sphere formation and inhibition of tumor formation in xenograft tumor models …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings correlates with earlier study reporting higher expression of OCT4 in premalignant and malignant cervical tumors; and its association with poor disease‐free survival and overall survival in patients with cervical cancer . The results holds significance as literature suggests the importance of OCT4 expression in resistance to radiotherapy in tumor cells and as predictors of poor survival . These support the hypothesis that OCT4 works as an oncogene in cervical carcinogenesis; more so when the knockdown of OCT4 have been shown to result in tumor cell apoptosis, decreased tumor sphere formation and inhibition of tumor formation in xenograft tumor models …”
Section: Discussionsupporting
confidence: 90%
“…47 The results holds significance as literature suggests the importance of OCT4 expression in resistance to radiotherapy in tumor cells and as predictors of poor survival. 48 These support the hypothesis that OCT4 works as an oncogene in cervical carcinogenesis 49 ; more so when the knockdown of OCT4 have been shown to result in tumor cell apoptosis, decreased tumor sphere formation and inhibition of tumor formation in xenograft tumor models. 43 To conclude, the present patient based investigation clearly underlines the significance of the viral oncoprotein E6telomerase reactivationcancer stem-cell (especially OCT4) axis in the susceptibility and severity of CaCx with underlying HPV16 infection.…”
Section: Discussionsupporting
confidence: 62%
“…However, further studies revealed that not only meiotic genes but also the key genes of early embryogenesis were induced by genotoxic treatments in various tumour cell lines, (both male and female), and associated with reversible polyploidy [30-32]. ESC-like gene signatures were also revealed in aggressive primary tumours [33-36] and it was shown that neoplastic non-stem cells could spontaneously convert into CSCs through epigenetic regulation [37-40]. …”
mentioning
confidence: 99%
“…Superficially, expression level of SOX2 was higher in tissues from patients with radiation-resistance compared with those with radiation-sensitivity, suggesting that SOX2 was a biomarker of unfavorable therapeutic reactivity 51 . Overexpression of SOX genes, such as SOX4 , in Caski cell lines also decreased the treatment efficacy of cisplatin by up-regulating the drug efflux transporter gene ABCG2 52 .…”
Section: Sox Genes In Gcsmentioning
confidence: 97%